Development of Learning Multimedia Using Macromedia Flash 8 in PAI Subject at SMP - Muhammad Fadhli Herman; Fetri Yeni J (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
Based on observations at a junior high school in Padang, it was found that Islamic Religious Education learning still felt boring. The factor that caused this boredom because the media used by teachers were still using traditional media. The solution to this problem requires the latest media that is fun for students. This study focused on the objective of examining the syntax of designing learning multimedia using Macromedia Flash 8 technology and the validity of the products developed. The type of research in this study is development research. The subjects of the trial in this study were one Islamic Religious Education teacher in grade VIII and two classes (control class and trial class) totaling 40 (fourty) students. The data collection techniques in this study were observation and questionnaires. The data analysis technique in this study was the analysis of the validity of the material, media, and language. The results of the study showed that the syntax of product design started from needs analysis, data collection, study of the use of Macromedia Flash 8, planning, making multimedia with Macromedia Flash 8, implementation of media in the field, and media evaluation. While the results of the product validity showed that the product was valid. The research results recommendations show that products made using Macromedia Flash 8 are very valid and very suitable for use in schools.┬á